2009
DOI: 10.1021/jp905162r
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Dielectric Relaxation Study at Ambient and Elevated Pressure of Molecular Dynamics of Pharmaceutical: Indomethacin

Abstract: Broadband dielectric measurements on the pharmaceutical indomethacin (IMC) were performed at ambient and elevated pressure. Data on molecular dynamics collected at ambient pressure are in good agreement with that published in the literature. In the glassy state, there is a well-resolved secondary relaxation with Arrhenius activation energy E(a) = 38 kJ/mol. This commonly observed relaxation process (labeled gamma) is of intramolecular origin because it is pressure-insensitive. Closer analysis of the ambient pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
140
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 127 publications
(161 citation statements)
references
References 78 publications
21
140
0
Order By: Relevance
“…In contrast to the spectra of normal liquids below 1.0 THz [13][14][15], e 00 (m) of the glassy IMC does not show the tail of the dielectric relaxation processes. This is mainly because the relaxation processes shift to a lower frequency range due to the liquid-glass transition [1,2]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to the spectra of normal liquids below 1.0 THz [13][14][15], e 00 (m) of the glassy IMC does not show the tail of the dielectric relaxation processes. This is mainly because the relaxation processes shift to a lower frequency range due to the liquid-glass transition [1,2]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…IMC easily undergoes a liquid-glass transition at the glass transition temperature, T g = 315 K upon cooling from the melt. It then exhibits physical properties similar to typical structural glasses [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…1). Individuals treated with such drugs are relieved of fever, pain, stiffness and swelling [9]. Several studies have also shown that indomethacin is an immunomodulator that augments macrophage, T cell, and natural killer cell activities and regulates the production of cytokines.…”
mentioning
confidence: 99%